Social determinants and health-related needs of pregnant refugees and asylum seekers = Soziale Determinanten und medizinische Bedarfe von schwangeren Flüchtlingen und Asylsuchenden - Gewalt, Sandra Claudia; Berger, Sarah; Bozorgmehr, Kayvan (Public-Health-Forum, 2018)
Migration experience and applying for asylum create unique health challenges for pregnant women and new mothers. Understanding the impact of social determinants of health on refugees and asylum seekers during pregnancy and early motherhood is important for equity and access to care. The World Health Organization’s framework on social determinants of health can serve research groups in strategically focusing their resources when investigating health needs, access to and provision of care.